2021
DOI: 10.1007/s11187-021-00506-4
|View full text |Cite
|
Sign up to set email alerts
|

The power of shared positivity: organizational psychological capital and firm performance during exogenous crises

Abstract: This study examines the influence of organizational psychological capital on the performance of small and medium-sized companies (SMEs) during crises. We argue that SMEs use their intangible resources to cope with difficult situations such as the COVID-19 pandemic. Therefore, we investigate how organizational psychological capital impacts performance and creative innovation through such intangible resources, namely, organizational citizenship behavior, solidarity, and cooperation. Methodologically, we combine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 161 publications
(362 reference statements)
4
49
0
Order By: Relevance
“…They concluded that PsyCap significantly impacted EP ( Gao et al, 2021 ). Grözinger et al (2021) reasoned that PsyCap was an essential psychological resource and analyzed it using a structural equation model. The results showed that PsyCap had a significant positive impact on EP ( Grözinger et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that PsyCap significantly impacted EP ( Gao et al, 2021 ). Grözinger et al (2021) reasoned that PsyCap was an essential psychological resource and analyzed it using a structural equation model. The results showed that PsyCap had a significant positive impact on EP ( Grözinger et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… Grözinger et al (2021) reasoned that PsyCap was an essential psychological resource and analyzed it using a structural equation model. The results showed that PsyCap had a significant positive impact on EP ( Grözinger et al, 2021 ). In short, PsyCap plays a positive role in EP according to a relevant literature review ( Digan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The more grounded the innovation capacity controlled by a company, the more successful its performance [41]. The link between innovation management and SME performance has been extensively analyzed, and in most cases, it shows the existence of significant impacts on economic and business performance [74]. Strategic innovation management is concerned with the use of appropriate strategic management techniques and measures to maximize the impact of the company's innovation activities for business growth and performance [75].…”
Section: The Management Of Innovation and Its Effects On The Economy ...mentioning
confidence: 99%
“…This suggests that psychological capital at work has a positive effect on organizational outcomes. Recent research suggested that the positive effect of psychological capital remains during the pandemic [29,30].…”
Section: Introductionmentioning
confidence: 99%